2013
DOI: 10.1248/bpb.b12-01012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Antiemetic Aprepitant in Japanese Patients Receiving High-Dose Chemotherapy Prior to Autologous Hematopoietic Stem Cell Transplantation

Abstract: For patients receiving high-dose chemotherapy, a 5-hydroxytryptamine 3 receptor antagonist combined with dexamethasone is a standard antiemetic therapy. Despite this prophylactic anti-emetic treatment, many patients still suffer from uncontrollable emesis. In this study, we retrospectively evaluated the antiemetic effectiveness and safety of aprepitant (a neurokinin-1 receptor antagonist) in addition to 5-HT 3 antagonist in Japanese patients with hematologic malignancy receiving high-dose chemotherapy prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Eleven papers, reporting results of clinical trials, that explored the effectiveness of a certain prophylaxis for CINV in patients undergoing HDMel conditioning for autologous SCT are included (Table 1). Of these 11 studies, 2 are randomized, comparative, and prospective [7,18], 6 are single-arm prospective [7,12,15,16,18,20], 2 are comparative and retrospective [10,19], and 1 is single-arm retrospective [13] ( Table 1). From these experiments, only aprepitant, fosaprepitant, and olanzapine were compared to standard therapy in the setting of HDMel.…”
Section: Efficacy Of Combination Antiemetic Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven papers, reporting results of clinical trials, that explored the effectiveness of a certain prophylaxis for CINV in patients undergoing HDMel conditioning for autologous SCT are included (Table 1). Of these 11 studies, 2 are randomized, comparative, and prospective [7,18], 6 are single-arm prospective [7,12,15,16,18,20], 2 are comparative and retrospective [10,19], and 1 is single-arm retrospective [13] ( Table 1). From these experiments, only aprepitant, fosaprepitant, and olanzapine were compared to standard therapy in the setting of HDMel.…”
Section: Efficacy Of Combination Antiemetic Therapymentioning
confidence: 99%
“…The retrospective comparative study by Uchida M. et al [19] was small, n of 48 with only 15 patients treated with HDMel conditioning, and compared a two-drug aprepitant + granisetron against granisetron alone. It is important to note that both regimens were steroid-free.…”
Section: Efficacy Of Combination Antiemetic Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…It can be combined with dexamethasone and a 5-HT3 receptor antagonist [10][11][12] . Recently, several studies have reported that aprepitant exhibited antiemetic effects during treatment involving HDCT prior to APBSCT [13][14][15][16][17][18] . These results indicated that aprepitant should be considered for CINV prophylaxis, although there is limited evidence supporting its use in this context [8,9] .…”
mentioning
confidence: 99%